Happy Seeder technology reaches over500,000 farmer households with 1.3 million ha in north-west India - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
CCAFS, CIMMYT, Sonalika tractors, Tata Trusts and other partners have invested to promote Happy Seeder technology in 7 districts of northwest India. This technology contributes to increased yields and farmer profits, and conserves water and nutrients. It also reduces air pollution and greenhouse gas emissions from on-farm activities.